Separate but Unequal: Immigration Detention in Canada and the Great Writ of Liberty - Anstis, Siena; Blum, Joshua; Will, Jared (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2017)
Canada maintains a separate legal regime for immigration detainees who, until recently, were denied the right to seek release by way of habeas corpus. This denial of one of the most deeply entrenched rights at common law and under the Canadian Charter of Rights and Freedoms was justified by the proposition that the immigration detention scheme is “separate but equal”—that it provides an adequate remedy such that habeas corpus is not necessary. Perhaps unsurprisingly, this “separate but equal” regime has failed to provide basic procedural and substantive protections that are available in other Canadian legal regimes where liberty is at stake. However, in 2015, the Court of Appeal for Ontario reignited the availability of habeas corpus as a remedy to indefinite detention in the immigration context in Chaudhary v. Canada (Public Safety and Emergency Preparedness). By reversing a line of cases that had confined immigration detainees to review by an administrative tribunal and judicial review in the Federal Court, Chaudhary has opened the door to the superior courts for immigration detainees. This article provides a review of the immigration detention system in Canada, the applicable legislation, procedures, and case law, and canvasses the impact of Chaudhary on the rights of immigration detainees. It then considers the benefits of habeas corpus as a litigation strategy, the role it has played in debunking the “separate but equal” myth, and suggests other potential issues now ripe for further litigation.